Evaluation of the Satu Sehat Health Pass (SSHP) Feature and Follow- Up Measures among Hajj Pilgrims at the Surabaya Embarkation in 2025 - Suroro, Niertara Awliya; Indradmojo, Christyaji (Proceeding Annual Symposium on Hajj and Umrah Medicine, 2026)
The Satu Sehat Health Pass (SSHP) is a digital innovation developed by the Ministry of Health of the Republic of Indonesia to integrate the health data of Hajj pilgrims at the national level through the Satu Sehat platform. This study aims to evaluate the level of SSHP utilization and assess the health follow-up of Hajj pilgrims at the Surabaya Embarkation in 2025. The method used was a quantitative approach with a descriptive cross-sectional design. Data were obtained from the reports of the Hajj Organizing Committee (PPIH) at the Surabaya Embarkation and the Satu Sehat database, including the number of pilgrims who completed and did not complete SSHP data entry, as well as health follow-up measures such as additional examinations, medical referrals, and the completeness of medical documentation. Preliminary findings indicate that although the overall compliance with SSHP data entry is relatively high, it remains uneven across age groups and regions of origin. Pilgrims who did not complete SSHP data entry tended to encounter obstacles in the follow-up process, including delays in examinations and inconsistencies in medical data. This evaluation is expected to provide an overview of the effectiveness of SSHP implementation and serve as a basis for improving the health monitoring system for Hajj pilgrims in the future.